2014
DOI: 10.1161/circulationaha.113.003142
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Obesity and Associations With Stroke and Myocardial Infarction in Women in the Years After Childbirth

Abstract: A disturbingly low rate of temporal decline in coronary heart disease mortality has been observed among women aged 35-44 years, compared with men and older women. 1 Additionally, women aged <45 years have an adverse prognosis after myocardial infarction as compared with men and older women, 2 and women 31-50 years old have a poorer prognosis than men after ischemic stroke.3 Further insight into cardiovascular risk factors and the prognosis of cardiovascular disease in young women is warranted, as requested by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…This is comparable with a recent Danish study of obese women that showed a 2.6-fold increase in risk for myocardial infarctions and a 1.9-fold increase in risk for stroke after 4.5 years of follow-up [18]. A similar increase in risk for men has been described in a prospective study of more than 3000 men between 18 and 30 years old, where BMI was found to be directly associated with myocardial systolic dysfunction after 25 years of follow-up [19].…”
Section: Discussionsupporting
confidence: 90%
“…This is comparable with a recent Danish study of obese women that showed a 2.6-fold increase in risk for myocardial infarctions and a 1.9-fold increase in risk for stroke after 4.5 years of follow-up [18]. A similar increase in risk for men has been described in a prospective study of more than 3000 men between 18 and 30 years old, where BMI was found to be directly associated with myocardial systolic dysfunction after 25 years of follow-up [19].…”
Section: Discussionsupporting
confidence: 90%
“…Not only overt pregnancy complications, but also more benign conditions, such as obesity, were associated with an increased risk for atherosclerotic morbidity. In young women, obesity during pregnancy was associated with an increased risk of ischaemic stroke and myocardial infarction in the years after childbirth . Likewise, in the current study obesity during pregnancy was independently associated with an increased risk of atherosclerotic hospitalizations.…”
Section: Discussionsupporting
confidence: 65%
“…30 About 6.1 (4.6-7.6) years of life were lost for young, obese women, aged 20-39 years, compared to 0.9 (0.1-1.7) years for those aged 60-79 years. Now, there is evidence that excessive weight among mothers carries additional threats since prepregnancy obesity 31,32 Furthermore, young obese women put their children at risk. 33 Cardiac and vasculature structural changes of offspring resulting from maternal over-nutrition include endothelial dysfunction, 34 inflammation, 35 increased sympathetic tone, 36 and myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 99%